Penolakan Klaim Asuransi Pertanian dan Pertanggungjawaban Penyelenggara: Disharmoni Hukum Asuransi dan Perlindungan Konsumen - Hesti Dwi Astuti; Purnama Sidiq (Jurnal Penelitian Hukum De Jure, 2026)
Claim rejections in the provision of agricultural insurance often give rise to legal issues as they lie at the intersection of the contractual insurance legal regime and consumer protection law. Most previous studies have focused on purely contractual aspects, leaving a gap in how the position of farmers is assessed within this dual legal regime. This situation has the potential to create legal uncertainty for farmers as policyholders. This study aims to analyze the legal status of farmers as consumers within the legal framework of agricultural insurance and to examine the liability of insurance providers for claim rejections from a consumer protection perspective. This study employs normative legal research, using a statutory and conceptual approach. Legal materials were obtained through a literature review of legislation, expert doctrine, and relevant legal literature. The results of the study indicate that farmers in agricultural insurance can be classified as consumers of financial services who are entitled to legal protection, particularly regarding information transparency, contractual fairness, and dispute resolution. Claim rejections cannot be based solely on a formal interpretation of policy clauses, but must take into account the principles of good faith and balance. If a claim is rejected without valid grounds, the insurer may be held liable under breach-of-contract or tort principles. The focus of this research lies in reconstructing the insurer’s legal liability, which is not based solely on contract law but is integrated with consumer protection instruments. Therefore, regulatory harmonization between insurance law and consumer protection is required to strengthen legal certainty, justice, and the benefits of the law in the administration of agricultural insurance.